Heterologous expression of SpsTAC2 in Arabidopsis affected branch angle and secondary vascular system development - Fangshu Niu; Mengru Yuan; Hongxia Zhao; Zhi Pang; Jie Yan; RuiXie Ning; Lin Shi; Fengqiang Yu; Dongshan Wei; Rong Yang; Runming Zhang; Haifeng Yang (Plant Signaling & Behavior)
To investigate the biological functions of Tiller Angle Control 2 (TAC2) in Salix psammophila. In this study, TAC2 was cloned from Salix psammophila, and an overexpression and subcellular localization expression vector for the SpsTAC2 gene was constructed. The SpsTAC2 gene was overexpressed in Arabidopsis and analyzed for phenotypic changes. The subcellular localization of SpsTAC2 was analyzed via Agrobacterium-mediated transient expression in onion (Allium cepa L.) epidermal cells. Phenotypic characterization of SpsTAC2 overexpressing Arabidopsis strains revealed that the branching angle of the transgenic strains was significantly greater than that of the wild type, and the anatomical structures of the stems and hypocotyls of the transgenic strains indicated that the vascular system of the transgenic strains developed more slowly than did that of the wild type. The subcellular localization of the SpsTAC2 gene revealed that the localization signals of the SpsTAC2 gene were mainly in the nucleus, and weak signals also appeared in the cell membrane, suggesting that the SpsTAC2 gene was mainly expressed mainly in the nucleus, with a small amount of expression in the cell membrane. This findings suggest that the SpsTAC2 gene influences the development of the branching angle of plants and xylem, and exerts its effects mainly in the nucleus and membrane. This study can help to characterize the regulatory effect of the TAC gene on the branching angle and explore its effect on the branching angle and vascular system development, and also help to explore the possible molecular regulatory mechanism, which can provide a theoretical basis for further elucidation of the mechanism of action of the IGT gene family.